Prognostic relevance of the right ventricular myo-mechanical index (RV-MMI) in patients with precapillary pulmonary hypertension - Greiner, Sebastian; Aurich, Matthias; Katus, Hugo; Mereles, Derliz (Open Heart, 2018)
Objective The aim of the prospective New-RV study was to evaluate a parameter for non-invasive quantification of right ventricular (RV) dysfunction in patients with precapillary pulmonary hypertension (PH) that yields prognostic information and is applicable in daily clinical routine. - Methods Sixty-five consecutive patients with precapillary PH under guideline conform therapy (43 women, 22 men) underwent clinical assessment, serological testing, as well as a comprehensive transthoracic echocardiography including strain imaging and a detailed assessment of RV haemodynamics. - Results The mean follow-up time was 844 days. Sixteen patients died during clinical follow-up. Right ventricular myo-mechanical index (RV-MMI) was calculated by right atrial size, mean RV pressure gradient and strain imaging of the RV free wall, and was measurable in all examinations. RV-MMI was tested for its diagnostic accuracy (sensitivity of 88% and specificity of 73% for an optimal cut-off value of ≤0.31 mm Hg*%; area under the curve=0.85), as well as its predictive value (HR=3.3, 95% CI 1.6 to 7.0, p<0.001), and was compared in detail with established parameters. RV-MMI and N-terminal pro-brain natriuretic peptide (NTproBNP)were independent predictors of survival (HR=2.9, 95% CI 1.4 to 6.2, p=0.006; and HR=2.6, 95% CI 1.5 to 4.6, p=0.001, respectively). - Conclusion In a cohort of patients with precapillary PH, the RV-MMI differentiates the outcome of patients better than other available non-invasive parameters of RV function by preload and afterload adjusted quantification. - Trial registration number NCT01230294.
Gesehen am 15.05.2019